The Expressive Function Of Figurative Language In The Novel Katarsis By Anastasia Aemilia: A Stylistic Study - Fataya Azzahra; Rurani Adinda; Fairuz Fairuz (Hasanuddin University, 2026)
Figurative language is not merely an aesthetic ornament, but a means of expressing psychological meaning in literary works. This study aims to examine the form and function of figurative language in Anastasia Aemilia's novel Katarsis through a stylistic approach. By connecting linguistic and aesthetic aspects, this study focuses on understanding the relationship between language, context, and emotional effects on readers. Using a qualitative descriptive method with the Simak and Catat techniques, as well as data in the form of quotations containing elements of metaphor, personification, simile, synesthesia, anatomicia, and metonymy, the data was analyzed based on the stylistic theories of Henry Guntur Tarigan and Gorys Keraf. Data in the form of quotations from the novel containing figurative language elements, such as metaphors, personification, similes, synesthesia, anatomicia, and metonymy, were analyzed based on the stylistic theories of Henry Guntur Tarigan and Gorys Keraf. This study used a qualitative descriptive method with observation and note-taking techniques. The results show that the use of figurative language in the novel Katarsis is very dominant and plays an important role in shaping the characters, building the atmosphere, and describing the inner conflicts and past traumas of the main characters. Metaphors and similes are the most frequently used figures of speech to express extreme emotions, inner turmoil, and tension in the storyline, both explicitly and implicitly. These findings confirm that figurative language in this novel is a medium for conveying complex psychological messages to readers, while also contributing to the development of modern literary stylistics studies in understanding the aesthetic and expressive functions of narrative prose.